THE RELEVANCE OF STRATEGIC JUSTIFICATION IN THE RISK MANAGEMENT SYSTEM TO INCREASE THE COMPETITIVENESS OF PHARMACY ORGANIZATIONS - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич; Черных, Наталья Степановна; Григорьева, Елена Борисовна (Medicine in Kuzbass, 2024)
The relevance of strategic justification in the risk management system of increasing the competitiveness of pharmacy organizations, which is an integral part of innovative competitor management, is considered. The library of competencies of pharmacy organization employees is presented, which contains competence models structured into clusters, competencies and indicators. The basis for competitor management is the human capital of employees, expressed in the form of key competencies. The ways of optimization of personnel management based on the use of quantitative indicators of the level of development of business competencies, representing the brand assets of the JSC, are proposed. It is shown that the success of a joint-stock company depends on many factors, including the formation of the quality of the organization’s work. However, the creation of a high reputation of a joint-stock company is a complex and lengthy process, consisting of determining the socially significant role of the organization, its individuality and identity, depending on the head. It is these factors that often become decisive in the market environment and are one of the urgent tasks of modern management, contributing to the competitiveness of JSC.